Understanding Synergistic Toxicity of Terpenes as Insecticides: Contribution of Metabolic Detoxification in Musca domestica - Scalerandi, Esteban; Flores, Guillermo A.; Palacio, Marcela; Defagó, Maria Teresa; Carpinella, María Cecilia; Valladares, Graciela; Bertoni, Alberto; Palacios, Sara María (Frontiers in Plant Science, 2018)
Essential oils, which are mixtures of terpenes, frequently show stronger insecticide activity, i.e., lower lethal dose 50 (LC50), than their most abundant terpenes. Synergy between terpenes provides a plausible explanation, but its demonstration has been elusive. In the present work, we look for an alternative explanation, by considering the influence of insect metabolic detoxification. Basically, we propose a model (metabolic model, MM) in which the LC50 of the major terpene in a mixture is expected to include a fraction that is detoxified by the insect, whereas a minor terpene would act unimpeded, showing a lower LC50 than when acting alone. In order to test this idea, we analyzed the effects of inhibiting the cytochrome P450 detoxification system with piperonyl butoxide (PBO), on the lethal concentration of terpenes as fumigants against Musca domestica. We found that, within a group of 10 terpenes [linalool, citronellal, (R)-α-pinene, 1,8-cineole, γ-terpinene, limonene, α-terpinene, (S)-β-pinene, thymol and (R)-pulegone], seven showed the LC50PBO (the lethal concentration for PBO-treated flies) between 1.7 and 12.4 times lower than the corresponding LC50 when P450 was not inhibited. Only in one case, that of (R)-pulegone, was the LC50PBO greater than the LC50, while two terpenes [(S)-β-pinene and thymol] showed no changes in toxicity. The increased activity of most terpenes (particularly linalool and citronellal) in PBO-treated flies supports our hypothesis that normally the LC50 includes a fraction of inactive compound, due to detoxification. Having previously determined that M. domestica preferentially oxidizes the most abundant terpene in a mixture, while terpenes in smaller proportions are poorly or not detoxified by the P450 system, we assessed whether the toxicity of minority terpenes in a mixture is similar to their activity under P450 inhibition. We chose suitable binary combinations in such a way that one terpene (in greater proportion) should be the target of P450 while the other (in smaller proportion) should intoxicate the fly with LC50PBO or similar. Combinations of 1,8-cineole-citronellal, 1,8-cineole-linalool, linalool-citronellal, (R)-pulegone-linalool, (R)-pulegone-1,8-cineole and (R)-pulegone-citronellal were assayed against M. domestica, and the LC50 of each mixture was determined and compared to values predicted by MM (considering the LC50PBO for minor component) or by the classical approach (LC50 for both components). The MM showed the best fit to the data, suggesting additive rather than synergistic effects, except for the combination of (R)-pulegone-citronellal that was clearly synergistic. Thus, the experimental data indicate that the insect preferentially oxidizes the major component in a mixture, while the terpene in lesser proportion acts as a toxicant, with higher toxicity than when it was assayed alone. These findings contribute to a deeper understanding of the higher toxicity of essential oils compared to their component terpenes and provide important information for the design of effective insecticides based on essential oils or terpenes.